Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 4 - Integrals - 4.4 Indefinite Integrals and the Net Change Theorem - 4.4 Exercises: 1

Answer

Verify $\int\frac{1}{x^2\sqrt{1+x^2}}dx=-\frac{\sqrt{1+x^2}}{x}+C$ We take the derivative of the right side of this equation and verify that it equals the inside of our integral. \begin{equation*} \frac{d}{dx}\left(-\frac{\sqrt{1+x^2}}{x}+C\right)=\frac{d}{dx}\left(-\frac{\sqrt{1+x^2}}{x}\right)+\frac{d}{dx}C=\frac{d}{dx}\left(-\frac{\sqrt{1+x^2}}{x}\right) \end{equation*} \begin{equation*} =-\frac{x\times\frac{1}{2}(1+x^2)^{-\frac{1}{2}}\times 2x-\sqrt{1+x^2}}{x^2} \end{equation*} \begin{equation*} =-\frac{\frac{x^2}{\sqrt{1+x^2}}-\sqrt{1+x^2}}{x^2}=-\frac{\frac{x^2-(1+x^2)}{\sqrt{1+x^2}}}{x^2}=-\frac{\frac{-1}{\sqrt{1+x^2}}}{x^2}=\frac{1}{x^2\sqrt{1+x^2}} \end{equation*} as desired.

Work Step by Step

Verify $\int\frac{1}{x^2\sqrt{1+x^2}}dx=-\frac{\sqrt{1+x^2}}{x}+C$ We take the derivative of the right side of this equation and verify that it equals the inside of our integral. \begin{equation*} \frac{d}{dx}\left(-\frac{\sqrt{1+x^2}}{x}+C\right)=\frac{d}{dx}\left(-\frac{\sqrt{1+x^2}}{x}\right)+\frac{d}{dx}C=\frac{d}{dx}\left(-\frac{\sqrt{1+x^2}}{x}\right) \end{equation*} \begin{equation*} =-\frac{x\times\frac{1}{2}(1+x^2)^{-\frac{1}{2}}\times 2x-\sqrt{1+x^2}}{x^2} \end{equation*} \begin{equation*} =-\frac{\frac{x^2}{\sqrt{1+x^2}}-\sqrt{1+x^2}}{x^2}=-\frac{\frac{x^2-(1+x^2)}{\sqrt{1+x^2}}}{x^2}=-\frac{\frac{-1}{\sqrt{1+x^2}}}{x^2}=\frac{1}{x^2\sqrt{1+x^2}} \end{equation*} as desired.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.